In‐depth analysis of pH‐dependent mechanisms of electromechanical reshaping of rabbit nasal septal cartilage. (2nd May 2014) - Kuan, Edward C.; Hamamoto, Ashley A.; Manuel, Cyrus T.; Protsenko, Dmitriy E.; Wong, Brian J. F.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Electromechanical reshaping (EMR) involves reshaping cartilage by mechanical deformation and delivering electric current to the area around the bend axis, causing local stress relaxation and permanent shape change. The mechanism of EMR is currently unclear, although preliminary studies suggest that voltage and application time are directly related to the concentration and diffusion of acid–base products within the treated tissue with little heat generation. This study aims to characterize local tissue pH changes following EMR and to demonstrate that local tissue pH changes are correlated with tissue damage and shape change. Study Design Ex vivo animal study involving EMR of rabbit nasal septal cartilage and biochemical estimation of tissue pH changes. Methods The magnitude and diffusion of acid–base chemical products in control (0V, 2 minutes), shape change (4V, 4 minutes; 6V, 1, 2, 4 minutes; 8V, 1, 2 minutes), and tissue damage (8V, 4, 5 minutes; 10V, 4, 5 minutes) parameters following EMR are approximated by analyzing local pH changes after pH indicator application. Results There is a direct relationship between total charge transfer and extent of acid–base product diffusion (P <0.05). A "pH transition zone" is seen surrounding the bend apex above 8V, 2 minutes. Colorimetric analysis suggests that small local pH changes (10−8 hydrogen ions) are at least partly implicated in clinically efficacious EMR. Conclusions These results provide additional insight into the translational applications of EMR, particularly the relationship among pH changes, shape change, and tissue injury, and are integral in optimizing this promising technology for clinical use. Level of Evidence N/A. Laryngoscope 124:E405–E410, 2014